A new species and notes on the genus Aphelocheirus (Hemiptera: Heteroptera: Aphelocheiridae) from China - Xie, Tong-Yin; Liu, Guo-Qing (Zootaxa, 2015)
This paper provides the description of a new species, Aphelocheirus menglaensis sp.nov. from Yunnan Province. A. gularis Horváth, 1918 and A. inops (Horváth, 1918) are reported from China for the first time. We also reviewed A. ellipsoideus Liu & Ding, 2005, include its macropterous forms and brachypterous female. Dorsal habitus photographs of the new species and A. ellipsoideus are provided and are accompanied by illustrations of male genitalic structures of both species and the ventral aspect of posterior abdominal segments of the female of only the new species.